2017
DOI: 10.1016/j.jaubas.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and surface modification of cellulose from underutilizedLuffa cylindricasponge: A potential feed stock for local polymer industry in Africa

Abstract: Cellulose was isolated from Luffa cylindrica sponge (LC) and modified by introducing acetyl ether functionality to its surface via simple reaction mechanism. L. cylindrica cellulose (LCC) and the acetyl ether modified L. cylindrica cellulose (LCS) were characterized using Fourier transformed infrared (FTIR), scanning electron microscopy (SEM), X-ray diffraction (XRD), particle size distribution, zeta potential, thermogravimetric analysis (TGA) and Brunauer-Emmett-Teller surface area analysis (BET). They were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The WAC of cellulose generally depends on various factors, including the degree of crystallinity, the presence of other substances (e.g., hemicellulose and lignin) in the cellulose matrix, and the accessibility of the hydroxyl groups [ 52 ]. Highly crystalline cellulose structures tend to have lower water absorption due to the limited availability of hydroxyl groups for hydrogen bonding [ 53 ]. Martinelli et al [ 52 ] claim that mature coconut fiber has more amorphous regions in its cellulose structure than young coconut fiber, which is also confirmed in this study ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The WAC of cellulose generally depends on various factors, including the degree of crystallinity, the presence of other substances (e.g., hemicellulose and lignin) in the cellulose matrix, and the accessibility of the hydroxyl groups [ 52 ]. Highly crystalline cellulose structures tend to have lower water absorption due to the limited availability of hydroxyl groups for hydrogen bonding [ 53 ]. Martinelli et al [ 52 ] claim that mature coconut fiber has more amorphous regions in its cellulose structure than young coconut fiber, which is also confirmed in this study ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The maximum MB and Pb 2+ ions sorption capacities (q max ) of the selected sorbents which calculated from the Langmuir model were compared with different sorbents in previous studies as presented in Table ( 4). The data indicated that the prepared sorbents have a good ability to remove MB and Pb 2+ ions from the solution.…”
Section: Effect Of the Initial Mb And Pb 2+ Ions Concentrationsmentioning
confidence: 96%
“…Nanocellulose (CN) yields a snowy-white powder. 22,23 2.2.2. Synthesis of ferric-modied nanocellulose composites.…”
Section: Synthesis Of Solid Nano-adsorbentsmentioning
confidence: 99%